Hearing the voice of children and young people with a learning disability during the Educational Health Care Plan (EHCP). Issue 2 (17th June 2019) - Pearlman, Sara; Michaels, Dina
Abstract : In England, eliciting the views, feelings and aspirations of young people with special education needs is central to the Special Education Reforms of 2015. However, there is little guidance on how to do this with young people who have intellectual and communication difficulties. In this research project, a questionnaire was developed and used as part of a structured interview, supported by Augmentative and Alternative Communication (AAC) with 22 young people with Moderate, Severe and Profound and Multiple Learning Disability (PMLD). The interview, which expolored the child's views about their lives at school and at home, was video recorded and clips were played to parents, teachers/and or Speech and Language Therapy (SALT) and NHS Psychology staff. It was hoped that this triangulated, evidence‐based approach to finding out their interpretations of what the child was communicating would provide a valid method. The results were analysed for efficacy and validity of the questionnaire and inter‐assessor reliability of ratings of the videos. Findings showed that by using both conventional and AAC methods, 11 out of the 22 young people were able to indicate responses to 75‐100% of the questions about their lives and preferences and 4 out of the 22 were able to answer 75‐100% of the section about hopes and aspirations for the future. We also found significant differences in ratings of 19 young people by school staff compared to family member and NHS researchers. This shows that it is essential to gather the different views of key people in the young person's environment. We have concluded that using video footage as a technique to elicit the voice of the child is to be recommended. One problem found with our questionnaire is that the young person's preferences are not equivalent to views and it would be essential to ask the young person about their experiences of the education they receive, which could then be fed back to their Education Health Care Plan (EHCP)/Annual review to give meaningful service‐user input. This would have to be done creatively and our questionnaire further adapted for those with more severe/PMLD.